Identifying genetic variation in candidate genes for heat stress and association thereof with growth performance in dusky kob (Argyrosomus japonicus) - Linder, Stephanie Jane (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.